Implications of Pleurotus ostreatus solid-state bioprocessing on the nutritional composition, protein structure, and anti-hypertensive and anti-inflammatory potential of local beans (Phaseolus vulgaris L.) - Sara Muñoz-Pina; Kateryna Khvostenko; Jorge García-Hernández; Ana Heredia; Ana Andrés (Current Research in Food Science)
Improving snacks formulation to make them more nutritionally balanced can support healthy growth and development in children. Specifically, this approach can be beneficial for preventing obesity and promoting overall metabolic health. Therefore, the effect of Pleurotus ostreatus solid-state fermentation on the nutritional quality, amino acid profile, and functionality of two traditional Valencian bean varieties were analyzed as potential ingredients for food formulation. Pleurotus ostreatus solid-state fermentation increased protein content by 23 % in Roget beans and 13 % in Herradura beans compared to the untreated beans, while simultaneously enhancing both essential and non-essential amino acid levels and reducing total carbohydrate content and antinutrient concentrations. Additionally, fermentation altered the amino acid profile, leading to an increase in amino acids such as valine, leucine, isoleucine, and tyrosine, compared to all other treatments. These amino acids play a crucial role in childhood health and development. Furthermore, fermented beans showed a 20 % angiotensin-converting enzyme inhibition, and Roget beans enhanced the inhibitory capacity of both cyclooxygenase-1 and cyclooxygenase-2 enzymes up to 90 %. Thus, fermented beans with Pleurotus ostreatus, specifically Roget beans, were identified as a novel ingredient for creating high-protein snacks specifically designed for children and teenagers.